PENGARUH PERUBAHAN BIAYA TRANSAKSI KARTU ATM (ANJUNGAN TUNAI MANDIRI) PADA TABUNGAN FAEDAH TERHADAP MINAT BERTRANSAKSI NASABAH DI BRISYARIAH KC SEMARANG - Imam Yahya; Retnandi Meita Putri (Economica: Jurnal Ekonomi Islam, 2016)
The more advanced information technology, the more frequently for banking institutions including BRI Syariah to follow and to use it as a part of service system, that is called as electronic banking. The growth of technology will change banking transaction system radically that eventually will change banking culture. The transaction through electronic banking will ease the customers in doing transaction therefore they are able to opt various services related to their need. Tabungan Faedah BRISyariah delivers affordable and easy service by using electronic banking in which all the transactions are free of charge. It starts from cash withdrawal, money transfer to BRISyariah ATM network, BRI Bank, Prima and Bersama. However, since May 6 2015, there was a transaction charge change especially for transaction in Issuer ATM that is BRI ATM, Prima and Bersama. Since the regulation was applied, the number of transactions also changed. According to the data of BRISyariah Issuer ATM transaction from January to December 2015, the total transaction declined. This research is aimed to discover the influence of transaction charge change of ATM card in faedah banking account to the costumers’ proclivity in BRISyariah KC Semarang.The transaction charge change of ATM card having positive influence and significance towards the costumer’s proclivity. The transaction charge such as cash withdrawal, money transfer, and balance check which is very expensive makes the customer’s proclivity declined. It is proved by the value of t-count is 2.878 t-table which is 2.024 by the degree od significance is 0.000 below 0.05.